Reappraising An Innovation in Rural Nursing Education 1984-Present - Alison Schell Witte (Online Journal of Rural Nursing and Health Care, 2015)
Presented at the 2014 International Rural Health & Rural Nursing Research Conference Co-Sponsored by the Montana State University College of Nursing and the Rural Nurse Organization (RN0).